Cyclopropane derivatives as potential human serine racemase inhibitors: unveiling novel insights into a difficult target. (3rd July 2016) - Beato, Claudia; Pecchini, Chiara; Cocconcelli, Chiara; Campanini, Barbara; Marchetti, Marialaura; Pieroni, Marco; Mozzarelli, Andrea; Costantino, Gabriele
Abstract: d -Serine is the co-agonist of NMDA receptors and binds to the so-called glycine site.d -Serine is synthesized by human serine racemase (SR). Over activation of NMDA receptors is involved in many neurodegenerative diseases and, therefore, the inhibition of SR might represent a novel strategy for the treatment of these pathologies. SR is a very difficult target, with only few compounds so far identified exhibiting weak inhibitory activity. This study was aimed at the identification of novel SR inhibitor by mimicking malonic acid, the best-known SR inhibitor, with a cyclopropane scaffold. We developed, synthesized, and tested a series of cyclopropane dicarboxylic acid derivatives, complementing the synthetic effort with molecular docking. We identified few compounds that bind SR in high micromolar range with a lack of significant correlation between experimental and predicted binding affinities. The thorough analysis of the results can be exploited for the development of more potent SR inhibitors.